Mindfulness as a mediator of relationship between burnout and psychological well-being among nurses - Nugroho, Alfian Fajar Budi; Nashori, Fuad (Universitas Mercu Buana Yogyakarta, 2024)
Many factors can influence psychological well-being of nurses, one of which is burnout that has a low correlation with psychological well-being. To better understand this relationship, additional variables are required. This study aims to determine the role of mindfulness as mediator the relationship between burnout and psychological well-being. This study involving mindfulness as a mediator of the relationship between burnout and psychological well-being. The subjects in this study were the 201 nurses at Regional Public Hospital Sleman selected by using a saturated sampling technique to make the entire population became the subject of the study. The instruments used in this study included RPWBS-42, MBI and MAAS then analyzing data using Path analysis. The results showed that mindfulness could be a mediator in the relationship between burnout and psychological well-being (p = .021). Burnout positively correlated with psychological well-being. Additionally, burnout has positively correlated with mindfulness. Last mindfulness positively correlated with psychological well-being. Mindfulness can explain the relationship between burnout and psychological well-being.